2017
DOI: 10.5120/ijca2017914776
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Stand-Alone Renewable Energy based Hybrid Power System for Remote Base Transceiver Station

Abstract: Due to the increasing number of mobile users, there is a huge demand of Base Transceiver Station (BTS) particularly in rural and semi urban areas. These BTS are operated on diesel generator (DG) and also connected with the existing grid supply. However, the grid supply is rarely available in most of the remote locations. Therefore, diesel generators are mainly used for providing the continuous supply to BTS and causes lot of emissions.In view of the above problems, a renewable energy based hybrid power system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Some of them used battery as backup power, which become expensive; while others don't have any plan for backup power. Some authors have shown that it is more economical if solar and/or wind is used in combination with biogas to form the micro-grid [3], [5], [7], [10]- [12], [14]- [16], [18], [20], [23], [46]; depending on the location type it is suitable to use wind , solar, biogas for power generation but what if the stored battery power is consumed, grid is not available for much time.Also, most of these microgrids require separate locations for both solar and biogas power plants, and this may increase the land need inciting added capital expense. Optimal sizing of the system with different renewable sources based on availability and demand using various multi-objective functions are shown in [1], [2], [5]- [7], [9], [10], [15], [16], [18], [19], [22], [47], [48], [50], [51] but there are no provisions for exigencies.…”
Section: A Motivation and Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them used battery as backup power, which become expensive; while others don't have any plan for backup power. Some authors have shown that it is more economical if solar and/or wind is used in combination with biogas to form the micro-grid [3], [5], [7], [10]- [12], [14]- [16], [18], [20], [23], [46]; depending on the location type it is suitable to use wind , solar, biogas for power generation but what if the stored battery power is consumed, grid is not available for much time.Also, most of these microgrids require separate locations for both solar and biogas power plants, and this may increase the land need inciting added capital expense. Optimal sizing of the system with different renewable sources based on availability and demand using various multi-objective functions are shown in [1], [2], [5]- [7], [9], [10], [15], [16], [18], [19], [22], [47], [48], [50], [51] but there are no provisions for exigencies.…”
Section: A Motivation and Problem Descriptionmentioning
confidence: 99%
“…Optimal sizing of the system with different renewable sources based on availability and demand using various multi-objective functions are shown in [1], [2], [5]- [7], [9], [10], [15], [16], [18], [19], [22], [47], [48], [50], [51] but there are no provisions for exigencies. A business model to some extent is developed in [4], [5], [9], [11], [17], [21]- [23], [25], [28], [34], [52] but they either include spot market rate, cost of equipment's or capital cost but lacks the real time cost of equipment's, interest rate, incentive. the proposed model has all the factors according to the current market rates including capital cost, land, incentive, equipment's, current electricity rate, risk factor, GHG emissions.…”
Section: A Motivation and Problem Descriptionmentioning
confidence: 99%
“…Telecom tower requires uninterrupted power supply. Base Transceiver Station (BTS) networks in rural areas continue to rely heavily on diesel generators because of paucity of reliable grid power and high cost of energy (Anand et al , 2017). This increases the focus on powering telecom towers through renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the major part of energy requirements is met through fossil fuels that create environmental pollutions including greenhouse gas emissions, global warming, acid rain, health issues, etc. (Anand et al, 2017a;Chauhan and Saini, 2016a;Kanase-Patil et al, 2011). In India, 70% of total population lives in rural areas and about 30% households do not have access of electricity.…”
Section: Introductionmentioning
confidence: 99%